Sosialisasi Perangkat Pembelajaran Matematika Berbasis CRT Motif Batif Bangun Datar Kelas 1 SDN 2 Ketandan - Puspa, Essa; Devi Puspita; Nisrina Luthfiyyah; Putri Zudhah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This community service project focuses on the socialization of mathematics learning devices based on the CRT (Culturally Relevant Teaching) approach, utilizing batik motifs for teaching flat shapes to first-grade students at SDN 2 Ketandan. The primary goal is to enhance students' understanding and appreciation of mathematical concepts through culturally relevant materials that resonate with their local heritage. The project involves training teachers on how to implement these learning devices effectively in the classroom, fostering an engaging and interactive learning environment. By integrating cultural elements into mathematics education, this initiative aims to motivate students and improve their academic performance while instilling a sense of pride in their cultural identity. The outcomes of this project will be evaluated through pre- and post-tests, as well as feedback from both teachers and students, ensuring that the implemented strategies are effective and beneficial